2021
DOI: 10.1155/2021/4276860
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Target Adaptive Tracking Based on GOTURN Algorithm with Convolutional Neural Network and Data Fusion

Abstract: With the advent of the artificial intelligence era, target adaptive tracking technology has been rapidly developed in the fields of human-computer interaction, intelligent monitoring, and autonomous driving. Aiming at the problem of low tracking accuracy and poor robustness of the current Generic Object Tracking Using Regression Network (GOTURN) tracking algorithm, this paper takes the most popular convolutional neural network in the current target-tracking field as the basic network structure and proposes an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With the introduction of the artificial neural network model [7][8][9][10], some scholars have optimized and improved the neural network model, and the proposed tracking algorithm has been greatly improved in accuracy and speed. In 2016, Valmadre et al proposed SiamFC [11], which trains a Siamese network to locate a sample image in a large search area to solve the similarity learning problem.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of the artificial neural network model [7][8][9][10], some scholars have optimized and improved the neural network model, and the proposed tracking algorithm has been greatly improved in accuracy and speed. In 2016, Valmadre et al proposed SiamFC [11], which trains a Siamese network to locate a sample image in a large search area to solve the similarity learning problem.…”
Section: Introductionmentioning
confidence: 99%
“…Human tracking aims to predict and locate the human's position in subsequent frames based on the initial human position in the first frame of the video, so as to estimate the movement track of the tracked human. After decades of development, human tracking technology has been widely used in the fields of security surveillance, human-robot interactions, sporting events, traffic monitoring [7][8][9][10], and has made great progress.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%